Collaborative Learning in the Texas Medicaid 1115 Waiver Program. Issue 6 (November 2016) - Revere, Lee; Semaan, Adele; Lievsay, Nicole; Hall, Jessica; Wang, Zheng M.; Begley, Charles
Abstract : Abstract: The Texas Medicaid 1115 Transformation Waiver reforms the state's safety net systems by creating a Delivery System Reform Incentive Payment incentive pool for innovative healthcare delivery. The Waiver supports the design and implementation of transformative projects. As part of the Waiver requirements, regions created Learning Collaboratives to collaborate on project implementation and outcomes. This paper describes the experience of one region in adapting the Institute for Healthcare Improvement Breakthrough Series (IHI BTS) model, as a framework for their Learning Collaborative. Implementation of the Learning Collaborative was systematic, multidimensional, and regularly evaluated. Some features of the IHI model were adapted, specifically longer Plan-Do-Check-Act cycles and the lack of a single clinical focus. This experience demonstrates the ability of a region to improve health from a more diverse perspective than the traditional IHI BTS Collaboratives. Within the region, organizations are connecting, agencies are building continuums of care, and stakeholders are involved in healthcare delivery. The initial stages show a remarkable increase in communication and enhanced relationships between providers. At the end of the 5-year Waiver, evaluation of the impact of the regional and cohort Learning Collaboratives will determine how well the adapted IHI BTS model facilitated improvements in the community's health.